2010
DOI: 10.2175/106143010x12609736966324
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Organic Nitrogen in Four Biological Nutrient Removal Wastewater Treatment Plants

Abstract: This study investigated the fate of nitrogen species, especially organic nitrogen, along the mainstream wastewater treatment processes in four biological nutrient removal (BNR) wastewater treatment plants (WWTPs). It was found that the dissolved organic nitrogen (DON) fraction was as high as 47% of soluble nitrogen (SN) in the low‐SN effluent plant, which limited the plant's capability to remove nitrogen to very low levels. A lower DON fraction was observed in high‐SN effluent plants. Effluent DON concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 20 publications
0
14
2
Order By: Relevance
“…It is likely that UV disinfection results in the breakdown of DON in a similar fashion to the breakdown that occurs during natural UV exposure (Simsek et al, 2013). This study's results differ from that of Sattayatewa et al (2010), which showed no changes in DON concentration after UV disinfection, which could be attributed to low UV dosage and contact time (Simsek et al, 2013). If a fraction of DON is converted to inorganic LMW-N as a result of UV disinfection, there will be less DON released into the environment.…”
Section: Resultscontrasting
confidence: 67%
See 2 more Smart Citations
“…It is likely that UV disinfection results in the breakdown of DON in a similar fashion to the breakdown that occurs during natural UV exposure (Simsek et al, 2013). This study's results differ from that of Sattayatewa et al (2010), which showed no changes in DON concentration after UV disinfection, which could be attributed to low UV dosage and contact time (Simsek et al, 2013). If a fraction of DON is converted to inorganic LMW-N as a result of UV disinfection, there will be less DON released into the environment.…”
Section: Resultscontrasting
confidence: 67%
“…UV disinfection alone has not shown to cause any concentration changes in DON (Sattayatewa et al, 2010). This could be attributed to the low UV intensity and duration of the system, which is too weak to oxidize organic matter (Sattayatewa et al, 2010). It is likely that different disinfection processes affect EDON's chemical properties, which could results in different interactions in the environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…His study showed median Total Kjeldahl N values for effluent of approximately 80 mg/l. In a recent study DON effluent was evaluated at 4 biological nutrient removal wastewater treatment plants, including one on the Neuse River, North Carolina (Sattayatewa et al 2010). They found that treatment plants could remove 60–80% of DON, but effluent contained between 0.5–2 mg/l DON.…”
Section: Resultsmentioning
confidence: 99%
“…rDON has emerged as a topic of interest for facilities that are required to meet strict effluent TN limits (<3 mg/L), since rDON can represent between 0.5 and 1 mg N/L of the effluent N (Sattayatewa et al, 2010). rDON has emerged as a topic of interest for facilities that are required to meet strict effluent TN limits (<3 mg/L), since rDON can represent between 0.5 and 1 mg N/L of the effluent N (Sattayatewa et al, 2010).…”
Section: Refractory Dissolved Organic Nmentioning
confidence: 99%